2019
DOI: 10.1029/2019jc015028
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Intermodel Diversity of CMIP5 Climate Models in Simulating East Asian Marginal Sea Surface Temperature in the Near Future (2020–2049)

Abstract: Using 14 Coupled Model Intercomparison Projections Phase 5 (CMIP5) climate models, we examined the intermodel diversity when simulating East Asian Marginal Seas (EAMSs) sea surface temperature (SST) in the near future period (2020–2049) under four different Representative Concentration Pathway runs. We classified two groups for the CMIP5 climate models: for models that simulate SSTs in the EAMS that are higher (H_EAMS) and lower (L_EAMS) than the ensemble mean, respectively. Results show that compared to L_EAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In this study, larger SST bias and inter-model diversity are found in the East/Japan Sea and the East China Seas. In the previous studies, it has been pointed out that the dynamical processes causing intermodel diversity in simulating East AMS SST during the near-future period (2020 -2049) may be not limited to local variables, but linked to Pacific Ocean basin-scale processes, and the inter-model diversity in simulating East AMS SST is influenced by both atmospheric and oceanic processes associated with the North Equatorial Current bifurcation latitude (Yi and Yeh, 2019). These findings suggest that in order to reduce AMS SST uncertainties from CMIP6 climate models, it is critical to correctly simulate the tropical Pacific mean state simulations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, larger SST bias and inter-model diversity are found in the East/Japan Sea and the East China Seas. In the previous studies, it has been pointed out that the dynamical processes causing intermodel diversity in simulating East AMS SST during the near-future period (2020 -2049) may be not limited to local variables, but linked to Pacific Ocean basin-scale processes, and the inter-model diversity in simulating East AMS SST is influenced by both atmospheric and oceanic processes associated with the North Equatorial Current bifurcation latitude (Yi and Yeh, 2019). These findings suggest that in order to reduce AMS SST uncertainties from CMIP6 climate models, it is critical to correctly simulate the tropical Pacific mean state simulations.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the amplitudes of seasonal variations are overestimated along the north coast of the Sea of Okhotsk, the western Arabian Sea, the eastern Bay of Bengal, and the Philippine Sea, with the largest positive biases of approximately 2°C occurring in the western Arabian Sea and the eastern Bay of Bengal (Figure 2I). Yi and Yeh (2019) pointed out that the East AMS SST bias is related to atmospheric teleconnections from the tropical to the western-to-central North Pacific. The East AMS SST bias is also associated with the bifurcation latitude of the North Equatorial Current, a low bifurcation latitude transports more warm water into the East AMS (Yi and Yeh, 2019).…”
Section: Causation Analysismentioning
confidence: 99%
See 3 more Smart Citations